FoxO3 an important player in fibrogenesis and therapeutic target for idiopathic pulmonary fibrosis - Hamza M Al‐Tamari; Swati Dabral; Anja Schmall; Pouya Sarvari; Clemens Ruppert; Jihye Paik; Ronald A DePinho; Friedrich Grimminger; Oliver Eickelberg; Andreas Guenther; Werner Seeger; Rajkumar Savai; et al. (EMBO Molecular Medicine)
Abstract Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal parenchymal lung disease with limited therapeutic options, with fibroblast‐to‐myofibroblast transdifferentiation and hyperproliferation playing a major role. Investigating ex vivo‐cultured (myo)fibroblasts from human IPF lungs as well as fibroblasts isolated from bleomycin‐challenged mice, Forkhead box O3 (FoxO3) transcription factor was found to be less expressed, hyperphosphorylated, and nuclear‐excluded relative to non‐diseased controls. Downregulation and/or hyperphosphorylation of FoxO3 was reproduced by exposure of normal human lung fibroblasts to various pro‐fibrotic growth factors and cytokines (FCS, PDGF, IGF1, TGF‐β1). Moreover, selective knockdown of FoxO3 in the normal human lung fibroblasts reproduced the transdifferentiation and hyperproliferation phenotype. Importantly, mice with global‐ (Foxo3−/−) or fibroblast‐specific (Foxo3f.b−/−) FoxO3 knockout displayed enhanced susceptibility to bleomycin challenge, with augmented fibrosis, loss of lung function, and increased mortality. Activation of FoxO3 with UCN‐01, a staurosporine derivative currently investigated in clinical cancer trials, reverted the IPF myofibroblast phenotype in vitro and blocked the bleomycin‐induced lung fibrosis in vivo. These studies implicate FoxO3 as a critical integrator of pro‐fibrotic signaling in lung fibrosis and pharmacological reconstitution of FoxO3 as a novel treatment strategy.